2022
DOI: 10.1002/adem.202101330
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Residual Stress in Laser Powder Bed Fused 316L: Effects of Interlayer Time and Scanning Velocity

Abstract: The control of residual stress (RS) remains a challenge in the manufacturing of metallic parts using the laser powder bed fusion process (LPBF). This layer‐by‐layer manufacturing approach gives rise to complex triaxial RS distributions, which require extensive characterization effort for a broader acceptance of LPBF in industry. This study focuses on the distribution of bulk triaxial RS and surface RS in LPBF austenitic steel 316L. The RS are determined by X‐ray and neutron diffraction to characterize the RS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…It has been, however, shown that the relaxation of the RS upon annealing is closely linked to the gradual dissolution of the cellular structure typical for 316L LPBF material. [ 44 ] Therefore, the optimal heat treatment to be performed to fully relax RS in 316L stainless steel without affecting its microstructure is still a subject for debate. Another way to investigate the effect of RS on the VHCF behavior is to embed artificial defects at different locations so that some defects would be located in areas experiencing tensile RS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been, however, shown that the relaxation of the RS upon annealing is closely linked to the gradual dissolution of the cellular structure typical for 316L LPBF material. [ 44 ] Therefore, the optimal heat treatment to be performed to fully relax RS in 316L stainless steel without affecting its microstructure is still a subject for debate. Another way to investigate the effect of RS on the VHCF behavior is to embed artificial defects at different locations so that some defects would be located in areas experiencing tensile RS.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, an increase in sub-grain size up to a factor 6, melt pool depth up to 20% and cooling rates up to a factor 12 were measured. Sprengel et al [10] investigated the effect of interlayer time and scanning velocity and their influence on the temperature distribution and resulting residual stresses in L-PBF manufactured 316L steel. In their experiments, it was found that at the surface, tensile residual stresses developed and these are directly related to the thermal history.…”
Section: Introductionmentioning
confidence: 99%
“…Heat input from the laser beam and heat transfer by conduction creates thermal cycles that can affect the microstructure and mechanical properties significantly [39]. In addition, high cooling rates and thermal gradients present in the LPBF process increase the magnitude of the residual stress [10,11]. This can leads to a geometrical non-conformity [12,13] and delamination of the as-build component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, for example, the contour method, neutron and synchrotron diffraction, the dissection technique, or the so-called deep-hole drilling [17]. Several investigations of AM components showed that high residual stresses and residual stress gradients could be expected, especially on the component surfaces [18,19], which also were in the range of the material yield strength. Due to this, as well as the fact that high tensile residual stresses; e.g., at notches, have a detrimental effect on the cold-cracking risk and performance of the component, investigations of the residual stresses should initially be analyzed predominantly by means of XRD.…”
Section: Introductionmentioning
confidence: 99%